Integrated Network Pharmacology and Metabonomics to Reveal the Myocardial Protection Effect of Huang-Lian-Jie-Du-Tang on Myocardial Ischemia - Li, Li; Dai, Weixing; Li, Wenting; Zhang, Yumao; Wu, Yanqin; Guan, Chenfeng; Zhang, Anye; Huang, Hui; Li, Yuzhen (Frontiers in Pharmacology, 2021)
Myocardial ischemia (MI) is one of the most common cardiovascular diseases with high incidence and mortality. Huang-Lian-Jie-Du-Tang (HLJDT) is a classic traditional Chinese prescription to clear “heat” and “poison”. To investigate the molecular mechanism and potential targets of HLJDT in treatment of MI, we used a deliberate strategy integrating the methods of network pharmacology, pharmacodynamics, and metabonomics. Firstly, by a network pharmacology approach, a global view of the potential compound–target–pathway network was constructed, which provided preliminary understanding of bioactive compounds and related targets of HLJDT for elucidating its molecular mechanisms in MI. Subsequently, the in vivo efficacy of HLJDT was validated in the rat model. Meanwhile, the metabolomics approach was applied to explore the differential metabolic markers induced, thus providing the metabolic mechanism of HLJDT in treating MI. The results demonstrated the myocardial protection effect of HLJDT on ischemia and clarified the multicomponent-multitarget mode. This study highlights the reliability and effectiveness of a network pharmacology-based approach that identifies and validates the complex of natural compounds in HLJDT for illustrating the mechanism for the treatment of MI.